Textile Chemistry - Bechtold, Thomas; Pham, Tung (De Gruyter STEM, 2019)
Textile Chemistry gives a detailed and explanatory overview on mainly chemical but also physical aspects of fabrics. It contains definitions, basic components and their properties, physicochemical processes, as well as chemical modification of textiles, highlighting the application of smart materials. The book also provides exercises and sample calculations, which makes it ideal for students and scientists in industry.